Assessment of the safety of dairy products by nitrate content depending on the season of production - Kukhtyn, Mykola; Laiter, Vyacheslav; Laiter-Moskaliuk, Svitlana; Horiuk, Yuliia; Dymchuk, Anatolii; Salata, Volodymyr; Khimych, Mariia; Kladnytska, Larysa (Eastern-European Journal of Enterprise Technologies, 2026)
This study quantifies nitrate content in dairy products depending on heat treatment, technological features, and seasonal factors. The task addressed was to assess the nitrate content in dairy products in order to prevent the entry of high concentrations. It was found that in the summer period, the nitrate content in drinking milk with different heat treatments did not exceed 5 mg/l. However, in the winter-spring period, an increase in the nitrate content in drinking milk was found, on average by 2.1 times, compared to milk in the summer period. This indicates that the nitrate content in drinking milk is mainly influenced by the seasonal factor. It has been shown that the nitrate content in fermented milk products (yogurt, kefir) was practically similar to that in drinking milk. At the same time, in fermented milk cheese, an average of 2 times less than in yogurt and kefir was found. This indicates that nitrates pass into whey during the production technology of fermented milk cheese. However, the influence of starter cultures used in the production technologies of yogurt, kefir, and fermented milk cheese on the content of nitrates was not detected. It was found that in soft cheeses in the winter-spring period, the amount of nitrates was on average 2 times higher, 16.5‒21.3 mg/kg, than in the summer period, while the effect of the season on the content of nitrates in hard and processed cheeses was not detected. In powdered milk, the concentration of nitrates was the highest ‒ 50‒80 mg/kg, compared to other dairy products, which indicates the concentration of dry substances during production. Thus, dairy products met the requirements of the EU regulation on the content of nitrates; the high concentrations detected in powdered milk indicate the need to control this product, especially when used for baby food